# Calculus

posted by .

Find the derivative: h(x)=7x/sqrt(5-2x)

Using the chain rule...I figured out my previous post.

• Calculus -

h(x) = 7x *(5-2x)^-1/2
dh/dx = 7 (5-2x)^-1/2
+ (7x)d/dx(5-2x)^-1/2

Use the chain rule on the second term

d/dx(5-2x)^-1/2 = (-1/2)(-2)(5-2x)^-3/2
= (5-2x)^-3/2

## Similar Questions

1. ### calc

find the derivative of y = sqrt(9 - 16x) Use the chain rule. First find the derivative of the sqrt, and multiply that by the derivative of what is contained inside. Cake. Use the chain rule. If we have y(x)=sqrt(9-16x) then y'=d/dx(sqrt(9-16x))*d/dx(9-16x) …
2. ### MoRe HeLp PlEaSe!! (calc)

Also can I get some help with this LONG, TIRESOME PROBLEM?
3. ### Math, Calculus

Find the derivative of the function. y= xcosx - sinx What's the derivative?
4. ### Calculus

Can anyone explain how to use the chain rule and power rule together to find the first derivative and please do these examples. f(x) = -3x^4/(sqrt(4x-8)) g(x) = ((2x+5)/(6-x^2)^4 g(x) = (8x^3)(4x^2+2x-3)^5 y = [1/(4x+x^2)^3]^3 Thank …
5. ### Calculus

How do I use the chain rule to find the derivative of square root(1-x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used?
6. ### calculus

find the derivative using quotient rule F(x) = (x - 7 x sqrt(x)) / sqrt(x)
7. ### calculus

Please help. Applying the chain rule, how do I find the derivative of f(x)=In(e^x-e^-x) (x>0) and then using this answer use the quotient rule to find the second derivative. I cannot do this so any answer greatly appreciated.
8. ### CAlculus

using chain rule find the derivative of y=xsin1/x
9. ### Calculus

1.) Find the derivative of tan (sec x). 2.) Find the derivative if 1/x in four ways, using the limit process, power rule, quotient rule and implicit differentiation. 3.) Show that the derivative of sec^-1 x is 1/(|x|*sqrt(x^2 -1)). …
10. ### Calculus

We just learned derivatives and now on the Chain Rule. y = r/[(sqrt)(r(sqrd)+1)] y' = [[(sqrt)(r(sqrd)+1)(r)'] - [(r)(sqrt)(r(sqrd)+1)']] / [(sqrt)(r(sqrd)+1)](sqrd) y' = (sqrt)(r(sqrd)+1) - r[1/2(r(sqrd)+1)(raised to -1/2)](2r) My …

More Similar Questions